Ocean Outreach in Australia: How a National Research Facility is Engaging with Community to Improve Scientific Literacy - Arthur, Benjamin; Roberts, Donna; Rae, Ben; Marrison, Matthew; McCleary, Hannah; Abbott, April; Musso, Barbara (Frontiers in Environmental Science, 2021)
Marine systems across the globe are experiencing myriad pressures with consequences for their health, management and the industries and communities that depend on them. Critical to improved management of our oceans and coasts is effective education and communication that ultimately leads to improved societal value of the world’s oceans. In Australia, the national scientific research agency, CSIRO, operates critical national research infrastructure such as the Marine National Facility (MNF), which also plays an important role in marine education, training and communication. The MNF Outreach Program seeks to strategically engage the community in marine science, identifying audience segments and developing programs, activities and content to meet their specific information needs. The program is structured around three specific audience segments: Purpose Seekers, Nurturers and Lifelong Learners. With both at-sea and shore-based activities and programs including the Indigenous Time at Sea Scholarship, CAPSTAN sea-training, Educator on Board, Floating Classroom, live ship-to-shore crosses and media and social media programming, the MNF Outreach program delivers meaningful engagement through experiential learning opportunities, rather than simply addressing knowledge deficits. As marine issues are varied and complex, marine communication and education approaches must be equally multifaceted, and a successful outreach program will have a spectrum of activities of varying resource intensity (such as cost, time and appropriately skilled personnel) which are matched to clear target audience segments. With increasing recognition of the importance of science communication in informing science literacy and policy, publicly funded national research facilities have an essential role to play by shifting from traditional research-only roles to also provide for targeted education and communication.